Perspektif Ulama Hadis Dan Fikih Terhadap Hadis Dhaif: Analisis Hadis Dhaif Dalam Fatwa Dewan Syariah Nasional Majelis Ulama Indonesia - Tsalis, Khodijah Nur; Mujib, Abdul; Bariki, Yusril; Tohir, Abdul Illah (Jurnal Hukum IUS QUIA IUSTUM, 2025)
This study examines the standards and provisions of fuqaha and muhaddisun in the use of daif hadith as a legal basis, as well as its application in the fatwa of the DSN-MUI with a focus on the sulh hadith and its implementation in the fatwa on Musyarakah Sharia Current Account Financing. This study highlights the lack of clear criteria and transparency in the use of daif hadith in the DSN-MUI fatwa which impacts the credibility and legal force of the fatwa . The purpose of the study is to describe the standards for the use of daif hadith according to the views of hadith and fiqh scholars, while also evaluating its application in the practice of DSN-MUI fatwas. The method used is normative legal research with textual and content analysis, including takhrij sanad and matan hadith as well as comparison with other valid evidence and established fiqh rules. The results of the study indicate differences of opinion between fuqaha and muhaddisun regarding the criteria and use of daif hadith as evidence. In the DSN-MUI fatwa , the frequently used hadith sulh has a weak sanad due to problematic narrators, but the text remains relevant and in accordance with sharia principles that encourage peaceful dispute resolution. In the fatwa on Sharia Musyarakah Current Account Financing, the implementation of the hadith sulh and other hadiths , some of which are weak, indicates the need for increased methodological accuracy and transparency in the inclusion of hadith status to maintain the credibility and accountability of fatwas , especially in facing the dynamic needs of contemporary sharia.